1996
DOI: 10.1007/bf00222951
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of genetic information from open-pollinated and control-pollinated progeny tests in two eucalypt species

Abstract: Genetic-parameter estimates and parental breeding-value predictions were compared from open-pollinated and control-pollinated progeny populations of Eucalyptus globulus and two populations of E. nitens. For E. globulus there were two types of open-pollinated populations (native stand open-pollinated and seed orchard open-pollinated) and two types of control-pollinated populations (intra-provenance and interprovenance full-sib families). For E. nitens there were two populations, a seed orchard open-pollinated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 9 publications
4
66
0
6
Order By: Relevance
“…Although a coefficient of relationship of 0.4 has been used for eucalypts (Brawner and Elizaul 2007;Greaves et al 1997;Volker et al 1990;Whiteman et al 1990), this coefficient of relationship supports earlier work by various authors (Griffin and Cotterill 1988;Griffin et al 1987;Hodge et al 1996;Verryn 1993), where it was suggested that seed orchard OP families are not true half-sib families, and may contain Molecular marker studies will further inform the levels of selfing in this population, and whether the levels of inbreeding are variable or more uniform.…”
Section: Coefficient Of Relationship and Outcrossing Ratesupporting
confidence: 73%
See 4 more Smart Citations
“…Although a coefficient of relationship of 0.4 has been used for eucalypts (Brawner and Elizaul 2007;Greaves et al 1997;Volker et al 1990;Whiteman et al 1990), this coefficient of relationship supports earlier work by various authors (Griffin and Cotterill 1988;Griffin et al 1987;Hodge et al 1996;Verryn 1993), where it was suggested that seed orchard OP families are not true half-sib families, and may contain Molecular marker studies will further inform the levels of selfing in this population, and whether the levels of inbreeding are variable or more uniform.…”
Section: Coefficient Of Relationship and Outcrossing Ratesupporting
confidence: 73%
“…The authors also investigated the effect of provenance in variance component estimation, i.e., families nested within provenance (family (provenance)) and families across provenances (Swain et al 2013b), but as this and other studies have shown that across-provenance estimates result in overestimates of additive genetic variance (Brawner and Elizaul 2007;Johnson 1996;Tibbits and Hodge 1998), this scenario was not included in this report. The scenarios investigated were: 1) Coefficient of relationship and outcrossingFollowing the approach of Squillace (1974), and extending his calculations, it has been shown that 30% selfing gives an average coefficient of relationship among open-pollinated (OP) progeny of 0.4 (Griffin and Cotterill 1988) and 25% selfing gives an average coefficient of relationship of 0.5 (Hodge et al 1996). Snedden et al (2007) assumed a coefficient of relationship of 0.33 in an E. grandis study where approximately 20% inbreeding was found.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations